2007
DOI: 10.1002/clc.20100
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Thoracic Sonography for Follow‐up Examination of Chronic Heart Failure Patients with Previous Decompensation

Abstract: SummaryBackground: Thoracic sonography searching for pleural effusion is helpful in diagnosing heart failure (HF) in emergency situations, but utility of this test for follow-up examination of chronic HF patient is unknown.Hypothesis: Thoracic sonography searching for pleural effusion may be suitable for monitoring deterioration in chronic HF outpatients during long-term follow-up.Methods: Patients with stable HF at the time of study entry, but with previous deterioration (n = 46) were recruited and followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…Recent studies have reported that ultrasound signs of pleural effusion were a common presenting heart failure-related sign for established heart failure patients during follow-up (Kataoka, 2007;Kataoka, 2011), and were strongly associated with the appearance of other heart failure-related symptoms and signs (Kataoka, 2010). The results also demonstrated that the ultrasound signs of pleural effusion had high diagnostic value for identifying heart failure status worsening, confirming that this sign was a useful marker in such patients during follow-up (Kataoka, 2010).…”
Section: Clinical Significance Of Ultrasound Pleural Effusion In Hearmentioning
confidence: 55%
See 2 more Smart Citations
“…Recent studies have reported that ultrasound signs of pleural effusion were a common presenting heart failure-related sign for established heart failure patients during follow-up (Kataoka, 2007;Kataoka, 2011), and were strongly associated with the appearance of other heart failure-related symptoms and signs (Kataoka, 2010). The results also demonstrated that the ultrasound signs of pleural effusion had high diagnostic value for identifying heart failure status worsening, confirming that this sign was a useful marker in such patients during follow-up (Kataoka, 2010).…”
Section: Clinical Significance Of Ultrasound Pleural Effusion In Hearmentioning
confidence: 55%
“…The patient is placed in a sitting position on a bed or chair, and chest ultrasound is performed on each hemithorax using a transducer through the intercostal space, and scanning is performed along the paravertebral, scapular, and posterior axillary lines (Kataoka & Takada, 2000;Kataoka, 2007;Piccoli et al, 2005;Waggoner et al, 1995). Using a high resolution (3.5-5.0 MHz) transducer applied to the chest wall, the parietal pleura lining the bony thorax and the visceral pleura covering the lung are seen just beneath the chest wall as two thin and bright echogenic lines.…”
Section: Chest Ultrasound Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Superimposition of changes caused by aging or other diseases, such as frequent leg edema in association with peripheral venous insuffi ciency in the elderly, might obscure the typical signs observed in younger patients. Age-related crackles in elderly patients with cardiovascular disease might be mistakenly diagnosed as a sign of heart failure deterioration, and a danger exists when diuretic therapy is inappropriately instituted.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related crackles in elderly patients with cardiovascular disease might be mistakenly diagnosed as a sign of heart failure deterioration, and a danger exists when diuretic therapy is inappropriately instituted. 4,14 Elderly patients with chronic heart failure and previous decompensation often have persistent pulmonary crackles, even during stable periods, 22 associated in some cases with the agerelated phenomena, not heart failure status. Whether crackles are related to cardiac dysfunction should be interpreted in light of other clinical tests including, for example, Doppler echocardiography, 7,8 serum BNP measurement, 17,22,25 or thoracic CT scans.…”
Section: Discussionmentioning
confidence: 99%